A systematic review and meta-analysis to compare the efficacy of conbercept with ranibizumab in patients with macular edema secondary to retinal vein occlusion. Issue 21 (22nd May 2020) - Liu, Weishai; Li, Yanjie; Cao, Rongxia; Bai, Zichao; Liu, Weiqin
Abstract: Background: The objective of this review and meta-analysis is to investigate the efficacy of conbercept and ranibizumab, combined with or without laser photocoagulation, in patients with macular edema secondary to retinal vein occlusion (RVO-ME). Methods: Several databases have been used to identify relevant publications. After screening, a meta-analysis was conducted to compare conbercept and ranibizumab with the support of RevMan 5.3 (Cochrane Library Software, Oxford, UK). Results: In this study, 9 randomized controlled trials and 6 retrospective trials were included with a total of 1180 patients. No significant difference was found in best corrected visual acuity (BCVA) or central macular thickness (CMT) in the baseline parameters [BCVA (weighted mean difference (WMD): –0.01; 95% confidence interval CI: –0.03 to 0.01; P  = .17), CMT (WMD: 20.14; 95% CI: –26.70 to 66.97; P  = .40). No significant differences were found in the improvements of BCVA and adverse events (AEs) between the 2 groups after injection of loading dosage [the 1st month BCVA (WMD: –0.01; 95% CI: –0.04 to 0.02; P  = .54), the 3rd month BCVA (WMD: –0.02; 95% CI: -–0.05 to 0.01; P  = .23), the 6th month BCVA (WMD: –0.02; 95% CI: –0.05 to 0.01; P  = .27), AEs (odds ratio: 0.84; 95% CI: 0.38 to 1.84; P  = .66)]. However, there were significant differences between conbercept and ranibizumab treatment in terms of CMT [1st month CMT (WMD: –11.70; 95% CI: –19.71 to –3.68; P  < .01), 3rd month CMT (WMD: –10.08; 95% CI: –15.62 to –4.53; P  < .01), 6th month CMT (WMD: –15.83; 95% CI: –22.88 to –8.78; P  < .01)] and the number of injections (WMD, –0.36; 95% CI: –0.68 to –0.04; P  = .03). Conclusion: The current pooled evidence suggested that both therapies of intravitreal conbercept and intravitreal ranibizumab with or without laser photocoagulation are effective in vision function in RVO-ME patients, and confirmed that conbercept has advantages over ranibizumab in terms of CMT and the number of injections for treating RVO-ME. In addition, conbercept has the statistically same visual gains and safety as ranibizumab in RVO-ME patients. Longer-term follow-up surveys on the safety and effectiveness of these 2 treatment regimens are required.